The dialectic of the prince and republicanism in Machiavelli’s thought (A study about the features of the cognitive method and political purposes) - الخطيب علي; هلا علي (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This research deals with the issue of Contradiction between two books: The Prince and The Discourses on Livy, by the Italian political thinker Niccolo Machiavelli. First The Prince discusses the system of monarchical rule based on the absolute powers of the prince, and in this book, Machiavelli discusses the necessary political skills in different political situations. On the other hand, The Discourses analyzes political theory and compares between the Republic and the Emirate, showing how political civilization has evolved. In this book, Machiavelli discusses Anacyclosis theory in politics, where one political system transitions to another according to a historical movement characterized by disturbance. The main paradox is that Machiavelli uses a similar epistemological approach in both books, with a clear difference in the topic. His political approach is based on the combination of experience and contemplation on history, which contradicts the ideal political perceptions inherited from the medieval age. He also relied on elevating self-experience and selfish interests in determining the best political decision according to expected political situations, all of this was accompanied by the decisive separation of politics from ethics. Thus, we can observe how Machiavelli’s description of the political community is based on view that includes a fierce conflict mixed with the competition of selfish desires and human chaotic ambitions. He saw that the political world is full of political tricks, deception, violence, and wars. Politics is the art of the possible, i.e. the art of the available possibilities according to the political reality, and it is not do of what ought to be, i.e. the ideal perception imposed on reality. Despite Machiavelli’s use of similar language and methodology in both of his books, so the relationship of the perception of the prince derived from the first book to the perception of the republican tendency derived from the Book of Discourses is the source of understanding and interpretation of Machiavelli’s general theory.